A de novo MAPRE2 variant in a patient with congenital symmetric circumferential skin creases type 2. Issue 2 (5th January 2020) - Feng, Jincai; Lan, Xiaoping; Shen, Jun; Song, Xiaozhen; Tang, Xiaojun; Xu, Wuhen; Ren, Xiang; Zhang, Hong; Yu, Guangjun; Wu, Shengnan
Abstract: Background: Congenital symmetric circumferential skin creases (CSCSC) was initially described five decades ago. Exome sequencing has recently revealed the genetic etiology of CSCSC. Pathogenic variants in TUBB (OMIM# 191130) and MAPRE2 (OMIM# 605789) have been linked to CSCSC1 (OMIM# 156610) and CSCSC2 (OMIM# 616734), respectively, in an autosomal dominant manner. Four pathogenic variants in MAPRE2 have been previously reported to be associated with CSCSC2. Methods: Whole‐exome sequencing (WES) has been performed and an in‐house pipeline was used to conduct a phenotype‐driven data analysis. All candidate variants were confirmed by Sanger sequencing. Results: Here we report a 2‐year‐old boy characterized by absent expressive speech, normal to mild over growth, facial dysmorphic features, remarkable circumferential skin creases on both forearms and ankles. WES disclosed a de novo missense MAPRE2 variant, c.518G>A (p.Arg173Gln), as the molecular cause of this complex phenotype. We described detailed clinical characterization of this patient and compared the available clinical data of individuals with MAPRE2 variants to demonstrate the phenotypic spectrum. Conclusion: Our study reports the first patient of Asian origin with CSCSC2 due to a pathogenic mutation of MAPRE2 and expands the clinical and genetic spectrum of CSCSC2. Abstract : A de novo MAPRE2 variant has been detected using whole exome sequencing in a patient with congenital symmetric circumferential skin creases, who has different clinical phenotypes compared with previously reported patients. This findings have expanded the clinical spectra of MAPRE2‐related disorder.